2006
DOI: 10.1182/blood-2006-03-006759
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene deletion demonstrates that the cell adhesion molecule ICAM-4 is critical for erythroblastic island formation

Abstract: Erythroid progenitors differentiate in erythroblastic islands, bone marrow niches composed of erythroblasts surrounding a central macrophage. Evidence suggests that within islands adhesive interactions regulate erythropoiesis and apoptosis. We are exploring whether erythroid intercellular adhesion molecule 4 (ICAM-4), an immunoglobulin superfamily member, participates in island formation. Earlier, we identified ␣ V integrins as ICAM-4 counterreceptors. Because macrophages express ␣ V , ICAM-4 potentially media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
113
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 40 publications
(34 reference statements)
1
113
0
1
Order By: Relevance
“…6 Thus, c-Maf and Palladin are important for erythroblastic islands in the embryonic stage, but their importance in the adult stage is still unconfirmed. However, a previous study found that ICAM-4 is critical for erythroblastic island formation in adult marrow, 41 but the role of ICAM-4 in the embryonic stage has been left for future study. Overall, previous studies and our results indicate that there might be different mechanisms or regulation processes or both between fetal liver and adult marrow/spleen erythroblastic island formation and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…6 Thus, c-Maf and Palladin are important for erythroblastic islands in the embryonic stage, but their importance in the adult stage is still unconfirmed. However, a previous study found that ICAM-4 is critical for erythroblastic island formation in adult marrow, 41 but the role of ICAM-4 in the embryonic stage has been left for future study. Overall, previous studies and our results indicate that there might be different mechanisms or regulation processes or both between fetal liver and adult marrow/spleen erythroblastic island formation and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data predict that the expression and/or interaction of key adhesion molecules on the surfaces of the red cells and macrophages may be sensitive to oxygen tension. It will therefore be interesting to determine whether adhesion molecules known to mediate macrophage-erythroblast interactions, such as ICAM-4 and ␣ 5 -integrin 33 or ␣ 4 -integrin and VCAM-1, 34 are altered in their expression or activity by changes in oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] However, macrophage colony-stimulating factor (M-CSF)-deficient op/op mice and CSFR -/-mice, which display reduced F4/80 tissue-resident macrophages, are characterized by hypocellularity of the bone marrow and reduced erythroid burst-forming units (BFU-E), 13 which indicates a major effect of macrophages on HSPC. In addition, erythroblast proliferation in bone marrow was unchanged in myeloablated mice and the ratios between the different stages during erythroblast maturation were comparable.…”
Section: Introductionmentioning
confidence: 99%